Author Correction: HuR regulates telomerase activity through TERC methylation - Hao Tang (Nature Portfolio, 2018)
In the original version of this Article, the affiliation details for Fan Yang were incorrectly given as ‘Key Laboratory of Regenerative Medicine of Ministry of Education, Institute of Aging and Regenerative Medicine, Jinan University, Guangzhou, 510632, China’ and ‘Leibniz Institute for Age Research - Fritz Lipmann Institute, Friedrich-Schiller University of Jena, Jena, 07745, Germany’. This has now been corrected in both the PDF and HTML versions of the Article.